The Analysis of Lateral Deformation of Diaphragm Wall by Using 2-Dimensional Finite Element Method in Basement Construction of the BRI Tower Medan - Putri, Vini Rizki Eka; Roesyanto, Roesyanto; Hasibuan, Gina Cynthia Raphita; Surbakti, Rudianto (Universitas Ibn Khaldun Bogor, 2024)
Land availability for multi-storey buildings can be managed by constructing a multi-storey building with a basement. The basement construction of Menara BRI Medan is surrounded by office buildings. The soil is composed of sand, medium sand, clay silt, and gravel, resulting in the construction of a retaining wall comprised of a diaphragm wall 17,50 meters deep with a wall thickness of 0,60 meters. During the deep excavation work, the diaphragm wall was reinforced by temporary supports (strut). The strut installation consists of 2 layers with a distance of 3 meters in between struts. This minimizes the deformation that occurs. The lateral deformation was calculated using the finite element method in PLAXIS 2D with Mohr-Coulomb soil modeling at drill point BH-02. The deformation results in PLAXIS 2D will be compared with the on-site monitoring results by taking Inclinometer-I2 measurements. The result of the lateral deformation of the diaphragm wall from the analysis using PLAXIS 2D modeling was found to be 7,72 mm. In addition, the lateral deformation value from the monitoring results during the measurement of inclinometer-I2 on site was 7,55 mm. However, during the comparison between the deformation results in PLAXIS 2D and the monitoring results on site, discrepancies were identified due to alterations of parameters during the execution of the deep excavation work.